Bahasa inggris sebagai jendela dunia: program pelatihan untuk anak-anak di Nagari Matua Mudiak Kecamatan Matur Kabupaten Agam - Kristian Burhan Burhan (Indonesian Institute For Counseling, Education and Therapy, 2025)
In the era of globalization, English language skills are key to accessing a wider range of information and opportunities. In Nagari Matua Mudiak, Matur District, Agam Regency, the low level of English proficiency among children hinders them from reaching their full potential. This program aims to bridge that gap and provide better access to education. The “English as a Window to the World” program is designed to train children in Nagari Matua Mudiak in English through interactive and engaging learning methods. The main objectives are to improve their speaking, listening, reading, and writing skills in English, as well as to foster an interest in learning foreign languages among children. With this training, it is hoped that children will be able to understand and use English in their daily lives. The outcomes of this program include: (1) Improving the English skills of children in the village, which can be measured through tests before and after training. (2) Establishing sustainable study groups so that children can continue to practice and interact in English. (3) Instilling confidence in communicating in English, which is expected to open up educational and career opportunities in the future. (4) Encouraging community participation in education, thereby creating a supportive learning environment. In addition, it also produces teaching materials and scientific publications in national journals.